2022
DOI: 10.47540/ijcs.v1i2.699
|View full text |Cite
|
Sign up to set email alerts
|

Kegiatan Trauma Healing Anak Yatim dan Disabilitas bagi Korban Covid-19 di Kabupaten Bombana

Abstract: This Internal Community Service Program aims to increase self-confidence and be able to return to normal life in the community. For this reason, the service team carries out Trauma Healing activities in the form of consultations and simulations for Covid-19 victims. This was done considering the unstable condition of the Covid-19 victims who took 3 months in a period of trauma due to the disease caused by the Covid-19 Virus and the views of the community and the nuclear family environment who saw the victims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Based on the findings of a study by the Global Burden of Disease, it is indicated that PWD constitute 15.3% of the global population (Husain, 2022). The data pertaining to PWD in Indonesia is derived from two comprehensive surveys, namely Basic Health Research (RISKESDAS) conducted by the Ministry of Health and Nasional Sosio-Economic Survey (SUSENAS) conducted by the Central Statistics Agency (BPS) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of a study by the Global Burden of Disease, it is indicated that PWD constitute 15.3% of the global population (Husain, 2022). The data pertaining to PWD in Indonesia is derived from two comprehensive surveys, namely Basic Health Research (RISKESDAS) conducted by the Ministry of Health and Nasional Sosio-Economic Survey (SUSENAS) conducted by the Central Statistics Agency (BPS) (Table 1).…”
Section: Introductionmentioning
confidence: 99%